Education and Optimization of Solar Power Plants (PLTS) in Mattiro Baji Village, Satangnga Island, Takalar Regency - Wahyu Ramadhani Gusti; Firman .; Supriadi .; Andi Alam Nur (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2026)
Mattiro Baji Village, located on Satangnga Island in Takalar Regency, is a coastal area facing limited access to electricity due to its geographical isolation from the mainland. The village’s power supply primarily relies on Solar Power Plants (SPP) and diesel generators. This community service program aimed to provide education and conduct operational inspections of functional SPP systems. The implementation method involved direct observation of three power systems: a main SPP with a capacity of 30 kWh, a smaller SPP with a capacity of 3 kWh, and a grid-connected SPP system supplying approximately 1 kWh. The inspection results showed that the main SPP experienced an inverter failure, while the small SPP remained operational, albeit with reduced efficiency due to accumulated dust and decreased battery capacity. In contrast, the grid-connected SPP system operated optimally. The other activity carried out was an educational session on the SPP, which was attended by eight representatives as participants based on the village head’s recommendation. This educational initiative successfully increased community awareness regarding the importance of regular maintenance, solar panel cleanliness, and efficient electrical load management. The average improvement, as measured through pre-test and post-test evaluations, reached 61%, indicating the effectiveness of the educational program. Through this approach, the sustainability of renewable energy systems in island communities can be strengthened, supporting Indonesia’s clean energy transition and equitable electricity access in remote, frontier, and outermost (3T) regions.